Paleomagnetic Evidence for a Partially Differentiated Ordinary Chondrite Parent Asteroid. Issue 7 (18th July 2019) - Bryson, J. F. J.; Weiss, B. P.; Getzin, B.; Abrahams, J. N. H.; Nimmo, F.; Scholl, A.
Abstract: The textures and accretion ages of chondrites have been used to argue that their parent asteroids never differentiated. Without a core, undifferentiated planetesimals could not have generated magnetic fields through dynamo activity, so chondrites are not expected to have experienced such fields. However, the magnetic remanence carried by the CV chondrites is consistent with dynamo‐generated fields, hinting that partially differentiated asteroids consisting of an unmelted crust atop a differentiated interior may exist. Here, we test this hypothesis by applying synchrotron X‐ray microscopy to metallic veins in the slowly cooled H6 chondrite Portales Valley. The magnetic remanence carried by nanostructures in these veins indicates that this meteorite recorded a magnetic field over a period of tens to hundreds of years at ∼100 Myr after solar system formation. These properties are inconsistent with external field sources such as the nebula, solar wind, or impacts, but are consistent with dynamo‐generated fields, indicating that the H chondrite parent body contained an advecting metallic core and was therefore partially differentiated. We calculate the thermal evolution of the chondritic portions of partially differentiated asteroids that form through incremental accretion across 10 5 to 10 6 years, finding this can agree with the measured ages and cooling rates of multiple H chondrites. We also predict that the cores of these bodies could have been partially liquid and feasibly generating a dynamo at 100 Myr after solar system formation. These observations contribute to a growing body of evidence supporting a spectrum of internal differentiation within some asteroids with primitive surfaces. Plain Language Summary: Asteroids formed during the first few million years of the solar system through the accretion of billions of millimeter‐sized solids. If this process occurred within the first ∼2 Myr of the solar system, the asteroid is thought to have partially melted, while if it occurred after this time, the asteroid is thought to have remained completely unmelted. Partial melting is an easy mechanism allowing an asteroid to differentiate into a rocky mantle and metallic core. Recently, this discrete nature of asteroid melting has been challenged by magnetic measurements of a group of unmelted meteorites that suggest they experienced magnetic fields generated in an asteroid core, hinting that their parent asteroid contained both melted and unmelted material and was therefore partially differentiated. Here, we show that a previously unmeasured type of unmelted meteorite recorded a magnetic field over a period of tens to hundreds of years at ∼100 million years after solar system formation. These timings make this a particularly robust observation that some unmelted meteorites experienced dynamo fields and originate from partially differentiated asteroids. This observation favors the episodic formation of some asteroids, potentially impacting our understanding of the thermal and structural history of the first planetary bodies in our solar system. Key Points: The Portales Valley H6 chondrite experienced a magnetic field with properties consistent with dynamo fields at  100 Myr after CAI formation This observation indicates that the H chondrite parent body contained an advecting metallic core, so was partially differentiated We model the thermal evolution of such bodies, finding that they can reproduce the measured ages and cooling rates of multiple H chondrites